Microwave-assisted boration of potato starch - Staroszczyk, H. (Polimery, 2009)
Granular potato starch was successfully borated with boric acid and sodium tetraborate decahydrate (borax) in a microwave-assisted solid state reaction. Products of starch boration reached (dependently on the conditions of the process) the maximal value of the degree of esterification (DE) equal to 0.27 when boric acid was applied, and 0.18 when borax was used. DTA, TG, DTG and FT-IR methods revealed that boration of starch provided boron esters or borate complexes. High-pressure size exclusion chromatography (HPSEC), DSC and X-ray diffraction showed that although the boration of starch caused changes in its macrostructure, the thermal stability of borated starch was enhanced even by 20°C when compared with native product, with larger stability exhibited by complexes than by esters. The thermal stability of the borated starch increased with an increase in DE. After modification, granularity of starch was retained, as was indicated by the scanning electron microscopy.